High quality transcriptome profiling confirms the transcriptional landscape of Treponema pallidum subsp. pallidum - Linda Grillová; Eli M. Carrami; William Roberts-Sengier; Nicholas R. Thomson (Scientific Reports)
Abstract Syphilis remains a critical global health challenge due to its potential for severe complications and the increase in its incidence rate over recent years. Until recently, the infectious agent of syphilis, Treponema pallidum subsp. pallidum (TPA), could not be cultured in vitro. Advances in co-culture techniques have enabled the effective long-term cultivation of TPA, providing a platform for studying its biology. Limited transcriptional data from TPA have been reported, and many genes in treponemal genomes are annotated based on in silico prediction of putative coding sequences without functional validation. To inform future syphilis vaccine development, experimental validation of in silico predicted genes coupled with functional annotation is necessary. This study used strand-specific RNA-sequencing to reconstruct a high-quality transcriptome profile of TPA, confirming the active transcription of genes previously annotated as hypothetical, paving the way for more accurate identification of vaccine target candidates. Our transcriptomic data also revealed, for the first time, the organization of genes into transcription units, an abundance of anti-sense RNAs, and transcripts from intergenic regions, providing crucial insights for future functional genomics studies of TPA.